Feeding Calcium Salts of Linseed Oil on Metabolic Status and Reproductive Traits in Grazing Dairy Cows - Iorio, Jesica Daniela (2024)
This experiment aimed to evaluate the effect of calcium salts of linseed oil (rich in alpha-linolenic acid (ALA, C18:3n-3) on metabolic and reproductive traits in high-producing dairy cows under grazing. Thirty-six Holstein dairy cows were randomly assigned, in a complete block design, to receive ALA supplementation (0.85 kg∙day−1 of calcium salts of linseed oil) or to remain as untreated control (CON). The concentrate was formulated to offer the same amount of energy across treatments (CON cows received an extra kg of corn to compensate for the higher energy density of ALA treatment). A PMR + Alfalfa pasture was offered to all cows at the same time. A fixed time artiﬁcial insemination (FTAI) at 80 DIM, preceded by a Presynch plus Ovsynch protocol was implemented for the first service and later, on return to estrus, heat detection and artiﬁcial insemination (AI) were performed. Pregnancy diagnosis was checked at 30, 42, 60, and 90 d after AI. Blood and milk samples were taken biweekly. Treatment affected plasma cholesterol concentration (160.36 vs. 186.70 mg∙dl−1, p = 0.03, for ALA and CON, respectively) and on size of corpus luteum (CL, 17.6 vs. 13.7 mm, p = 0.02, for ALA and CON, respectively). Supplementation tended (p = 0.136) to increase conception rate by 200 DIM (81.69% vs. 55.43% in ALA and CON cows, respectively). However, treatment had no effect (p > 0.05) on body weight (BW), body condition score (BCS), and circulating levels of beta-hydroxybutyrate (BHBA), glucose, insulin, growth hormone (GH) and insulin-like growth factor (IGF-I). Our results suggest that supplementation with calcium salts of linseed oil could enhance ovarian function without affecting energy metabolism in early lactation dairy cows.